Pygmy and Giant Dipole Response Function in Neutron Rich Nuclei at Finite Temperature - Sahin, Ersin; Bozkurt, Kutsal; Sirin, Mehmet (AMER INST PHYSICS, 2009)
We investigate pygmy and giant dipole resonance (PDR-GDR) for the case of neutron rich soft nuclei Ni-68 and heavy nuclei Pb-208 using effective nucleon-nucleon Skyrme interactions SLy7 and KDEO at finite temperature. We use the mean-field theory (HF) and employ the random phase approximaton (RPA) in a coordinate space. We then compare the PDR calculations for the different Skyrme interactions with their experimental results. We find that the PDR and GDR strength distribution depends sensitively on temperature, and especially for Ni-68 the collective effects almost disappear at T=4 MeV.
Keywords: pgymy and giant dipole resonance; Hartree-Fock plus mean-field; Skyrme interactions; finite temperature; DEPENDENCE; EXCITATION; Physics